The effect of organizational politicization on proactive behavior - an analytical study of the opinions of a sample of workers in the Karbala Cement Factory - Mithaaq Hatif Abdul Sada Fatlawi; Hussein Sobeih Moheisen (Iraqi Journal for Administrative Sciences, 2024)
This research seeks to test the effect of organizational politices on proactive behavior. The research presented a theoretical framework for organizational politices and proactive behavior, and analysis of the relationship between them through the opinions of a sample of workers in Karbala Cement Factory, A total of 260 questionnaires were distributed to a number of workers in Factory. The number of retrieved responses was (221) and the statistical analysis (204) and response rate (92%). A statistical set of statistical methods available in the statistical programs (Spss v.25) and (Amos v.21). The results of the statistical analysis showed the availability of organizational politicization and proactive behavior in the Karbala Cement Plant, and the results indicated that there was a correlation between the research variables and a negative correlation effect